STUDI PUSTAKA TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR SISWA - Dedi Saputra; Wildana Wargadinata; Shofil Fikri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine various factors that influence student learning outcomes based on a review of previous research literature. This research employs a descriptive qualitative approach using a literature review method by collecting data from credible scientific journals. The findings of this study indicate that: 1. Positive internal factors include motivation, interest in learning, and students’ physical-psychological condition. 2. Positive external factors consist of parental support, teachers’ teaching methods, and the learning environment. 3. Negative internal factors include anxiety, low self-confidence, and health problems. 4. Negative external factors comprise family economic issues, unsupportive peer groups, and less engaging learning strategies. 5. Student learning success is significantly influenced by a combination of internal and external factors simultaneously.